Optical trapping using mode-locked fiber laser Au-NP coated side-polished fiber - Mahmud, N.N.H.E.N.; Awang, N.A.; Abdul Kahar, R.; Tajudin, M.N.H.M.; Zulkefli, N.U.H.H. (Elsevier, 2024)
We introduce a new technique for manipulating silica gel particles suspended in a water-based solution using a stable mode-locked fiber laser (MDFL). We coated a side-polished fiber (SPF) with Au-NP which acts as a saturable absorber (SA). A stable MDFL was achieved at an operating wavelength of 1557.8 nm and a repetition rate of 60.8 MHz. The optical trapping of sub-micrometer-sized silica gel particles revealed remarkable characteristics of the optical force. This force was driven by the presence of surface plasmon polaritons (SPP) in the Au-NP SPF, which played a crucial role in facilitating the manipulation of silica gel particles. Specifically, the SPP generated a gradient optical force, propelling the particles toward the propagation region. Throughout the optical trapping process, we observed wavelength shifts towards higher values in the spectrum, ranging from 1557.8 to 1563.1 nm. To quantify the optical force, we conducted computational and experimental analyses, yielding a force range of 0.16 to 2.10 fN. The percentage errors associated with these measurements ranged from 3.37% to 7.48%. Importantly, simulation results closely align with the experimental findings, establishing a robust foundation for future applications.